EARLY DIAGNOSIS OF ACUTE DIFFUSE PULPITIS, TREATMENT SUCCESS - V. Chetruș; I. Roman; S. Ciobanu (Romanian Society of Oral Rehabilitation, 2014)
Purpose of the work: The efficacy of early diagnosis of acute diffuse pulpitis, errors and complications that may occur during treatment. Acute diffuse pulpitis as a result of etiologic factors remains one of the most common dental emergencies that are not diagnosed and treated in time lead to an increased risk in the development of periodontal complications. The study was conducted on a group of 35 patients who were sent for treatment at the Department USMF dentistry, Nicolae Testemiţanu'', of which 12 (34.28%) were female, 23 (65.71% ) males, 16 smokers (45.71%) and 19 smoking (54.28%), 1 patient (2.85%) during orthodontic treatment, aged 19-42 years. The methods of treatment used vital extirpation 32 cases (91.42%), and in 3 cases (8.57%) non vital extirpation. In this study-positive results were achieved demonstrating the success of treatment as a result of an earlier diagnosis of disease data. In this study it can be stated with certainty that diffuse acute pulpitis is a severe clinical evolution, requiring immediate therapeutic treatment to prevent complications.